Shariah Governance, Maqasid al-Shariah, SMEs Performance: The Role of Gender and Age - Sri Lestari Kurniawati; Wiwik Lestari; Linda Purnama Sari; Titis Puspitaningrum Dewi Kartika (Journal of Economics, Business, and Accountancy Ventura, 2020)
This study's primary objective is to develop shariah governance and maqasid alshariah models in improving the performance of SMEs in Surabaya, Indonesia. The sampling technique used is the purposive sampling method, and the analysis model used is the Structural Equation Model (SEM). The results show that creating a conducive pre-condition/situation, Sharia governance principles, and ethics, and code of conduct have insignificant influence on SMEs' performance. In contrast, maqasid al-shariah has a significant influence on the performance of SMEs. Besides, the results also show that gender positively moderates the influence of ethics and code of conduct on the performance of SMEs. In contrast, age negatively moderates the influence of the creation of conducive pre-condition/situation and ethics and code of conduct on SMEs' performance. The results of this study are expected to be used as input for SMEs to improve their performance. SMEs need to understand the Sharia governance indicators and increase their understanding of maqasid al-shariah in running their business.